STRATEGI DAN TANTANGAN IMPLEMENTASI TOTAL QUALITY MANAGEMENT PADA SEKOLAH MENENGAH KEJURUSAN (SMK) DI INDONESIA (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Quality assurance in vocational education has become a strategic issue in enhancing the competitiveness of Vocational High School (SMK) graduates in Indonesia. One widely adopted approach is Total Quality Management (TQM). This study aims to analyze the strategies, challenges, and impacts of TQM implementation at the SMK level in Indonesia using a systematic literature review (SLR) approach. Articles were collected using the Publish or Perish software based on Google Scholar within the 2015–2025 publication period and were selected through the PRISMA model, resulting in 12 articles that met the inclusion criteria. The findings indicate that TQM implementation strategies in SMKs include strengthening quality assurance systems and stakeholder involvement, developing human resources and leadership, adopting international quality standards (ISO), creating a conducive work environment, and providing adequate facilities and infrastructure. The main challenges involve human resource readiness, financial constraints, disparities in facilities between public and private SMKs, and weak integration of quality management systems. The implementation of TQM has been shown to positively impact teacher quality, curriculum relevance, student achievement, and customer satisfaction. Therefore, TQM has strong potential as a strategic framework for fostering a sustainable quality culture in vocational education.